Dredged gravels from the central Arctic Ocean - Schwarzacher, Walther, author.; Hunkins, Kenneth L. (Kenneth Leland), 1928- author.; Lamont Geological Observatory, issuing body.
"Prepared for Geophysics Research Directorate, Air Force Cambridge Research Laboratories" "AF 19 (604) 2030." Includes bibliographical references (pages 20-22). Mode of access: Internet.